3-Dimensional magnetic resonance imaging of the freely moving human eye. (November 2020) - Franceschiello, Benedetta; Di Sopra, Lorenzo; Minier, Astrid; Ionta, Silvio; Zeugin, David; Notter, Michael P.; Bastiaansen, Jessica A.M.; Jorge, João; Yerly, Jérôme; Stuber, Matthias; Murray, Micah M.
Highlights: Eye motion is a major confound for MRI in neuroscience or ophthalmology. We developed a novel 3D MRI protocol while the eye freely moves. We fully reconstruct videos of the moving eye and head. Validated image quality (<1 mm resolution) for motion and anatomical features. Technique runs on a standard clinical setup; wide deployment is readily feasible. Abstract: Eye motion is a major confound for magnetic resonance imaging (MRI) in neuroscience or ophthalmology. Currently, solutions toward eye stabilisation include participants fixating or administration of paralytics/anaesthetics. We developed a novel MRI protocol for acquiring 3-dimensional images while the eye freely moves. Eye motion serves as the basis for image reconstruction, rather than an impediment. We fully reconstruct videos of the moving eye and head. We quantitatively validate data quality with millimetre resolution in two ways for individual participants. First, eye position based on reconstructed images correlated with simultaneous eye-tracking. Second, the reconstructed images preserve anatomical properties; the eye's axial length measured from MRI images matched that obtained with ocular biometry. The technique operates on a standard clinical setup, without necessitating specialized hardware, facilitating wide deployment. In clinical practice, we anticipate that this may help reduce burdens on both patients and infrastructure, by integrating multiple varieties of assessments into a single comprehensive session. More generally, our protocol is a harbinger for removing the necessity of fixation, thereby opening new opportunities for ethologically-valid, naturalistic paradigms, the inclusion of populations typically unable to stably fixate, and increased translational research such as in awake animals whose eye movements constitute an accessible behavioural readout.